Anasisis Minat Wirausaha Berdasarkan Jenjang Pendidikan Vokasi Pada Bidang Teknik Mesin - Erika Ayunda Prihatin; Indah Widiastuti; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Entrepreneurship is one aspect that affects economic growth in Iindonesia. Students are the next generation who are expected to be able to create entrepreneurs in the future. The purpose of this research is to analyze entrepreneurial interest based on vocational education level in mechanical engineering and the factors driving this interest. This research uses a mix-method that combines a quantitative approach and a qualitative approach. The subjects of the research were Class XII students of State 2 Vocational High School in Surakarta, department of mechanical engineering, totaling 120 people and D3 Mechanical Engineering students at Sebelas Maret University, totaling 57 people. Data collection techniques to determine the entrepreneurial interest of students (quantitative data) using the questionnaire method while knowing the factors that influence entrepreneurial interest (qualitative data) using the interview method. Analysis of data for quantitative data using descriptive analysis and for qualitative data using thematic analysis. The result showed that the majority of students wanted to be entrepreneurs but a different levels of time. Factors that influence entrepreneurial interest are divided into two, namely internal factors and external factors. The internal factors driving entrepreneurial interest are motivation that comes from the individual’s self and enthusiasm to face risk challenges. External factors driving or family, entrepreneurial interest are motivation the arises due to the influence of friends or family, entrepreneurial experience and entrepreneurship education.